2006
DOI: 10.2174/187153006778250037
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Glutathione and IGF in a Hyperglycaemic Cell Culture Model of Fibroblasts: Some Actions of Advanced Glycaemic end Products (AGE) and Nicotine

Abstract: The aim of this investigation was to establish potential oxidative effects of glucose, advanced glycation end products (AGE) and nicotine (N) in a fibroblast cell culture model using the anti-oxidants glutathione (G) and insulin like growth factor (IGF). Assays of androgen metabolites were used as biomarkers of healing in this context. Confluent monolayer cultures of human gingival fibroblasts were established in 24 well multiwell plates and incubated in Eagle's MEM for 24h using two radiolabelled androgen sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…For example, IGF protected fibroblasts and intestinal epithelial cells, and HGF have a protective effect on retinal pigment epithelium in oxidative injury [10][11][12]. Also, FGF, PEDF and IL-6 reduce the epithelial cell death induced by hydrogen peroxide [14,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, IGF protected fibroblasts and intestinal epithelial cells, and HGF have a protective effect on retinal pigment epithelium in oxidative injury [10][11][12]. Also, FGF, PEDF and IL-6 reduce the epithelial cell death induced by hydrogen peroxide [14,24].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few reports involving the antioxidant action of stem cells, some evidences support a protective effect of cytokines on the epithelial cells during oxidative injury. For example, insulin like growth factor (IGF) reportedly protects fibroblasts and intestinal epithelial cells from free radicals [10,11]. HGF has a protective effect on retinal pigment epithelium in oxidative stress induced by glutathione depletion [12].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal effective concentration of G was established at 3 µg/mL (G3). Similar optimal effective concentrations of N and G were established in fibroblast cultures in our previous work [29,43]. The optimal effective concentration of enamel matrix derivative (E) was established using serial concentrations of 15, 30, 45, 60 and 75 µg/mL in MG63 osteoblasts with MEM and radiolabeled 14C-testosterone (T) as substrate.…”
Section: Methodsmentioning
confidence: 94%
“…The pathogenesis and progression of periodontal disease is escalated by advanced glycaemic end products AGE (Takeda et al 2006), receptor for AGE (RAGE) which is highly expressed in periodontal tissues and AGE/RAGE interactions in uncontrolled diabetics. Using a diabetogenic cell culture model of well characterized osteoblasts, it has been demonstrated that the oxidative effects of AGE and nicotine were overcome by the antioxidant glutathione (Rahman & Soory 2006). Preliminary studies in pro-oxidant cultures of oral periosteal fibroblasts and well characterized osteoblasts demonstrated that co-enzyme Q10, phytoestrogens and the antioxidant Pycnogenol derived from pine bark, attenuated oxidative stress induced by nicotine in this model (Figuero-Ruiz et al 2006); indicating a possible role for these antioxidants in the adjunctive therapy of inflammatory diseases characterized by a pro-oxidant profile.…”
Section: Mechanisms Affecting Dyslipidaemia Diabetes and Periodontitismentioning
confidence: 99%